A curious association of chronic homeopathic arsenic ingestion with nonspecific symptoms in a Swiss teenager (Swiss Medical Weekly, 2019)
Arsenic is a toxicant that has no dose threshold below which exposures are not harmful. Here I report a curious association of chronic homeopathic arsenic ingestion with nonspecific symptoms in a Swiss teenager. For about 4 years she had taken globules of a freely purchasable homeopathic remedy containing inorganic arsenic (iAs), infinitesimally diluted to D6 (average arsenic content per single globule: 0.85 ± 0.08 ng). In the previous 7 months she had taken 20 to 50 globules daily (average 30 ng arsenic daily). She complained of nausea, stomach and abdominal cramps, diarrhoea and flatulence, headache, dizziness, anxiety, difficulty concentrating, insomnia, snoring, leg cramps and fatigue, loss of appetite, increased thirst and sweating, reduced diuresis, weight gain, paleness and coolness of both hands with a furry feeling of the hands, eczema of the hands, arms and legs, conjunctivitis and irregular menstruation. The physical and laboratory examinations showed a body mass index of 30 kg/m2, acne vulgaris, bilateral spotted leukonychia, eczema of hands, arms and legs, non-pitting oedema of the legs, elevated plasma alkaline phosphatase activity, folate deficiency and severe vitamin D3 insufficiency. The arsenic concentration in her blood was